Herbivore and detritivore effects on rainforest plant production are altered by disturbance. Issue 13 (4th June 2019) - Prather, Chelse M.; Belovsky, Gary E.
Abstract: Consumer effects on rainforest primary production are often considered negligible because herbivores and macrodetritivores usually consume a small fraction of annual plant and litter production, even though consumers are known to have effects on plant production and composition in nontropical systems. Disturbances, such as treefall gaps, however, often increase resources to understory food webs, thereby increasing herbivory and feeding rates of detritivores. This increase in consumption could lead to more prominent ecosystem‐level effects of consumers after disturbances, such as storms that cause light gaps. We determined how the effects of invertebrate herbivores (walking sticks) and detritivores (litter snails) on understory plant growth may be altered by disturbances in a Puerto Rican rainforest using an enclosure experiment. Consumers had significant effects on plant growth, but only in light gaps. Specifically, herbivores increased plant growth by 60%, and there was a trend for detritivores to reduce plant growth. Additionally, plant biomass tended to be 50% higher with both consumers in combination, suggesting that herbivores may mediate the effects of detritivores by altering the resources available to detritivore food webs. This study demonstrates that disturbance alters the effects of rainforest consumers, and, furthermore, that consumer activity has the potential to change rainforest successional processes. Abstract : Although herbivores are generally considered to have negligible effects on plants and plant composition in the tropics, we show that herbivore selective feeding changes plant composition and growth.